Implementation of Secure Shell in Document Sharing Application with TCP/IP-Based Client Server - Barus, Della Rizkynta Br (PT. Technology Laboratories Indonesia (TechnoLabs), 2025)
The network laboratory module is being reviewed, in which the author conducted data exchange using a LAN cable system and the operating systems provided by Windows or Linux for document transfer and data transmission. The idea is to create software that will perform document transfer and data reception using a sharing medium. The aim is to simplify the process for computer users to send and receive transferred documents. The advantage of client-server software for uploading images and sharing images, documents, and data such as documents and other files is that a flash drive is no longer needed to transfer data, which could potentially contain viruses that could damage the data on the user's computer. Data security is enhanced through secure shell (SSH) connection settings for computers connected via a local area network (LAN). Document sharing security utilises SSH, a cryptographic network protocol designed to securely operate network services over insecure networks that could otherwise endanger data stored on the sender's or recipient's computer.